1994
DOI: 10.1038/ki.1994.301
|View full text |Cite
|
Sign up to set email alerts
|

A twelve year natural history of hepatitis C virus infection in hemodialyzed patients

Abstract: A prospective non-A, non-B follow-up program, implemented in a hepatitis B surface antigen-free dialysis unit, enabled us to report on the natural history of hepatitis C virus (HCV) infection in hemodialyzed patients between 1980 and 1992. For this program, every patient was prospectively monitored every two weeks for alanine amino transferase (ALT) activity, and every month for gammaglutamyl transpeptidase (GGT) activity and systematic collection of frozen sera. Sequences of stored sera from 217 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
3
5

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 30 publications
8
67
3
5
Order By: Relevance
“…11 Although the duration of anti-HCV positivity in these patients is not precisely known, it is likely to be short, as shown by the lack of cirrhosis, mild liver histologic findings, and the known risk of seroconversion to anti-HCV positive state while on hemodialysis in the absence of blood transfusion. 12,13 Our results of genotyping are in keeping with other reports that showed that type 1b and 4 are the predominant genotypes in this part of the world.…”
Section: Discussionsupporting
confidence: 80%
“…11 Although the duration of anti-HCV positivity in these patients is not precisely known, it is likely to be short, as shown by the lack of cirrhosis, mild liver histologic findings, and the known risk of seroconversion to anti-HCV positive state while on hemodialysis in the absence of blood transfusion. 12,13 Our results of genotyping are in keeping with other reports that showed that type 1b and 4 are the predominant genotypes in this part of the world.…”
Section: Discussionsupporting
confidence: 80%
“…The results from molecular biology investigations and epidemiological evaluation are complementary pieces of evidence for possible nosocomial transmission of HCV (16,18,19). This case emphasizes the risk of transmission and the importance of infection control procedures in hemodialysis units (22). It also highlights the usefulness of molecular epidemiological techniques for the investigation of outbreaks of HCV infection.…”
mentioning
confidence: 96%
“…Prospective studies mono-centric and multicenter helped establish the incidence of HCV seroconversion in hemodialysis [32,[37][38][39][40][41][42][43]. The annual incidence varies between studies and countries with low or zero rate in developed countries, and over 10% in emerging countries.…”
Section: The Seroconversion Of Hepatitis C Virus In Hemodialysismentioning
confidence: 99%